Pricing and Profitability Management A Practical Guide for Business Leaders - Julie M. Meehan; Michael G. Simonetto; Larry Montan, Jr.; Christopher A. Goodin (Singapore John Wiley & Sons (Asia) Pte. Ltd., 2011)
The practical guide to using pricing and profitability management to build a better business A comprehensive reference for any business professional looking to understand the capabilities and competencies required for effectively managing pricing and profitability, Pricing and Profitability Management explains how to determine the right approach, tools, and techniques for each of six key categories (pricing strategy, price execution, advanced analytics and optimization, organizational alignment and governance, pricing technology and data management, and tax and regulatory effectiveness). Exploring each category in detail, the book addresses how an integrated approach to pricing improvement can give a sustainable, competitive advantage to any organization. The ultimate how to manual for any executive or manager interested in price management, the book presents a holistic, comprehensive framework that shows how integrating these pricing categories into a cohesive program leads to impressive gains that cannot be achieved through a single-pronged approach. Presents a comprehensive framework for more effectively managing pricing and profitability Identities the six key categories of pricing and profitability management Shows you how to gain a competitive edge by managing pricing and profitability Taking a comprehensive view of pricing, companies can position themselves to tap a vast source of shareholder value--the ability to set and enforce profitable prices, not just once, but again and again in response to marketplace changes and evolving business needs--and this book will show you how.
Keywords: Business; Nonfiction; Pricing